Tempeh as a Cultural Heritage in Indonesia: Intergenerational Perception - Anwar, Khoirul; Maskar, Dadi H.; Prasetyo, Irene Nuariza; Kusumawati, Intan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to assess how people perceive tempeh. The study was conducted using an online self-administered questionnaire among 340 respondents aged between 11 and 58 years. The results showed that respondents perceived tempeh as an Indonesian cultural food (97.70%), a highly nutritious food (99.41%), and a superfood (86.47%), and 51.76% of respondents consumed 50 g of tempeh daily. Most respondents perceived tempeh to have economic impact (91.7%) and used it as a food for celebrations (95.29%), and there was no significant differences between generations (p<0.05). The conclusion is that tempeh is perceived as an Indonesian cultural food that has cultural, economic, and nutritional value.